Synthesis of highly selective lysosomal markers by coupling 2-(2′-hydroxyphenyl)benzothiazole (HBT) with benzothiazolium cyanine (Cy): the impact of substituents on selectivity and optical properties. Issue 47 (12th November 2019) - Abeywickrama, Chathura S.; Bertman, Keti A.; Mcdonald, Lucas J.; Alexander, Nicolas; Dahal, Dipendra; Baumann, Hannah J.; Salmon, Carrie R.; Wesdemiotis, Chrys; Konopka, Michael; Tessier, Claire A.; Pang, Yi
Abstract : A few HBT-Cy-containing fluorescent probes have been synthesized for lysosome visualization in live cells. Abstract : HBT-Cy 1 has been previously reported as a highly selective fluorescent probe for lysosome visualization in live cells. To further investigate the role of the structural components of HBT-Cy in lysosome selectivity, cyanine based fluorescent probe series (2–5 ) have been synthesized in good yields by connecting benzothiazolium cyanine (Cy) with 2-hydroxyphenylbenzothiazole (HBT) via a meta phenylene ring. Probes 2–5 exhibited exceptional photophysical properties including bright red-emission ( λ em ≈ 630–650 nm), a large Stokes shift (Δ λ > 130 nm) and high fluorescence quantum yields ( ϕ fl ≈ 0.1–0.5). Probes 2, 3, and 5 exhibited exceptional selectivity towards cellular lysosomes in NHLF and MO3.13 cells. Our further study revealed that the phenyl benzothiazolium cyanine component (6 ) was the lysosome directing group in the HBT-Cy probe structure. The attachment of the hydroxyphenyl benzothiazole (HBT) component to the HBT-Cy probe structure has significantly improved its photophysical properties. Lysosome probes 2, 3 and 5 exhibited excellent biocompatibility, quick staining, bright red fluorescence, and wash-free application for live cell imaging. These probes further exhibited excellent characteristics for bioimaging experiments including a non-alkalinizing nature, high biocompatibility, high photostability and long-term imaging ability (>4 hours).